An Unusual Location for Orbital Schwannoma: A Case Report - Mohammad Etezad Razavi; Mehrdad Motamed Shariati; Mostafa Fakoor (Clinical Case Reports)
ABSTRACT Orbital schwannomas are benign and slow‐growing tumors that constitute 1% of all orbital tumors. They arise from the sensory branch of the ophthalmic division of the trigeminal nerve and are hence more often found in superior orbit regions. In this case report, we presented a 34‐year‐old healthy man with proptosis in the right eye and diplopia. Imaging revealed a large, well‐circumscribed mass in the right medial rectus. The patient underwent surgical resection of the tumor, and the patient's symptoms resolved 5 days after surgery. Pathological and immunohistochemical evaluations confirm the diagnosis of schwannoma.